RAHASIA BANK BAGIAN DARI PROSES MONEY LAUNDRY - wagiman, wagiman; Susilo, M. Endriyo (Universitas Muhammadiyah Ponorogo, 2021)
The crime of money laundering is very detrimental to the public at large, because the crime will also be followed by other crimes, corruption, terrorism and drugs. The purpose of this research is to discuss the extent to which the Bank is involved in the money laundering process, so the researcher takes the theme Bank Secrets as part of the money laundering process. The method used is literature study with descriptive, exploratory, and analytical approaches. It can be concluded that, Bank Secrecy is everything related to information regarding depositors and deposits where the principle of bank secrecy aims to protect customers. Bank is a financial institution that runs its business based on the trust of its customers so that banks are required to be able to maintain the confidentiality of all data and information related to their customers, including information on financial transactions carried out by their customers. It is recommended that the bank should apply the Know Your Customer â€œKnow Your Customer principleâ€ properly accompanied by an adequate reporting system. If there is a suspicious flow of funds, it can work with related parties (PPATK, KPK and the Police) so that money laundering can be prevented as early as possible.